Filipino Labor Outmigration: A Preliminary Analysis - de Guzman, Arnel (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Exporting manpower has been a lucrative source of much-needed capital for the Philippine government. There has been a great push to send Filipinos over-seas to generate foreign exchange, alleviate the unemployment situation, and regain balance of payment deficits. Overseas contract workers, however, are exploited in various ways such as unfair wages and poor living conditions. The government's response, if any, to these exploitations are not enough as they see worker exportation as a short-term solution to national economic problems. Through organization and unity, over-seas workers must stand up and speak for themselves to gain the justice and representation they deserve.
Keywords: overseas workers; exploitation; migrant labor; foreign employment; remittances